No Late Arrivals Allowed! : An Analysis of the Timely Exercise of Denial of Benefits Clauses in International Treaties Ensuring Foreign Investment as an Objection to the Competence of Arbitral Tribunals in Investment Arbitration - Quiroz Arellano, Matías (2025)
This research seeks to address the question of why arbitral tribunals have interpreted treaties concluded by the United States as taking a pragmatic approach to the invocation of the denial of benefits clauses they contain. Thus, our hypothesis states that various of the arbitral tribunals that have interpreted these treaties adopting a pragmatic approach have interpreted these clauses following various methods of interpretation, among which (i) the literal method, (ii) the teleological method, and (iii) the functional method of interpretation are predominant. In this sense, the main objective of the research will be to identify the main grounds used by the arbitral tribunals when analyzing the moment of invocation of these clauses in this type of treaties. To this end, the methodology used is qualitative in nature and seeks to be mainly analytical of existing jurisprudence. The aim is to directly analyze the decisions of existing arbitration cases and, indirectly, the bibliographical sources that analyze the decisions of this case law.